Dari Sumber Informasi ke Galeri Pengetahuan Pendekatan Kearsipan pada Penyelenggaraan Pameran Arsip Statis - Adhie Gesit Pambudi (Arsip Universitas Gadjah Mada, 2017)
Conceptually, archival exhibition is not a part of core functions of an archival organization. However, it could give an enormous benefit for the community when it could transform archives from just a source of information into a source of knowledge. This study elaborates principles and ideal stages that should be conducted by archival institution in organizing archival exhibitions so that it could give knowledge to the audiences. It focuses on a proper achival management approach in conducting archival exhibition rather than other aspects such as design or estetique.